Locoregional therapies of cholangiocarcinoma - Sommer, Christof-Matthias; Kauczor, Hans-Ulrich; Pereira, Philippe L. (Visceral medicine, 2016)
Cholangiocarcinoma (CC) is the second most primary liver malignancy with increasing incidence in Western countries. Currently, surgical R0 resection is regarded as the only potentially curative treatment. The results of systemic chemotherapy and best supportive care (BSC) in patients with metastatic disease are often disappointing in regard to toxicity, oncologic efficacy, and overall survival. In current practice, the use of different locoregional therapies is increasingly more accepted. Methods: A review of the literature on locoregional therapies for intrahepatic cholangiocarcinoma (ICC) was undertaken. Results: There are no prospective randomized controlled trials. For localized ICC, either primary or recurrent, radiofrequency ablation (RFA) is by far the most commonly used thermal ablation modality. Thereby, a systematic review and meta-analysis reports major complication in 3.8% as well as 1-, 3-, and 5-year overall survival rates of 82, 47, and 24%, respectively. In selected patients (e.g. with a tumor diameter of ≤3 cm), oncologic efficacy and survival after RFA are comparable with surgical resection. For diffuse ICC, different transarterial therapies, either chemotherapy-based (hepatic artery infusion (HAI), transarterial chemoembolization (TACE)) or radiotherapy-based (transarterial radioembolization (TARE)), show extremely promising results. With regard to controlled trials (transarterial therapy versus systemic chemotherapy, BSC or no treatment), tumor control is virtually always better for transarterial therapies and very often accompanied by a dramatic survival benefit and improvement of quality of life. Of note, the latter is the case not only for patients without extrahepatic metastatic disease but also for those with liver-dominant extrahepatic metastatic disease. There are other locoregional therapies such as microwave ablation, irreversible electroporation, and chemosaturation; however, the current data support their use only in controlled trials or as last-line therapy. Conclusion: Dedicated locoregional therapies are commonly used for primary and recurrent ICC as well as liver-only and liver-dominant extrahepatic metastatic disease. Currently, the best evidence and most promising results are available for RFA, HAI, TACE, and TARE. In cohort studies, the overall survival rates are similar to those obtained with surgery or systemic therapies. Prospective randomized controlled trials are warranted to compare safety and efficacy between different surgical, interventional, and systemic therapies, as well as their combinations.
Gesehen am 08.05.2020